57.6k views
0 votes
What is the solution of the system? use elimination . -12x-y=6 17x+y=4

User KristianB
by
5.1k points

1 Answer

3 votes
To clarify the systems of equations:


-12x - y = 6

17x + y = 4

We already have opposite coefficients for y, so combine the two equations together:


5x = 10

Divide both sides by 5 to get x by itself:


x = 2

Because we now know x, we can plug it into one of the equations.

We will plug this value into the first equation:


-12(2) - y = 6


-24 - y = 6

Add 24 to both sides.


-y = 30

Divide both sides by -1 to get y by itself.


y = -30

Using elimination, x = 2 and y = -30.
User Abhishek Dujari
by
5.7k points